2012
DOI: 10.1371/journal.pone.0038188
|View full text |Cite
|
Sign up to set email alerts
|

Key Physiological Parameters Dictate Triggering of Activity-Dependent Bulk Endocytosis in Hippocampal Synapses

Abstract: To maintain neurotransmission in central neurons, several mechanisms are employed to retrieve synaptically exocytosed membrane. The two major modes of synaptic vesicle (SV) retrieval are clathrin-mediated endocytosis and activity-dependent bulk endocytosis (ADBE). ADBE is the dominant SV retrieval mode during intense stimulation, however the precise physiological conditions that trigger this mode are not resolved. To determine these parameters we manipulated rat hippocampal neurons using a wide spectrum of sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 43 publications
3
39
0
Order By: Relevance
“…EM examination after intense nerve stimulation reveals endosome-like structures or cisternae much larger than regular vesicles (Figure 3 b i ) (6, 44, 5658, 78, 79). Some of these structures take up extracellular horseradish peroxidase or FM dyes, suggesting their endocytic origin (Figure 3 b i ).…”
Section: Endocytosis Modes: Supporting Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…EM examination after intense nerve stimulation reveals endosome-like structures or cisternae much larger than regular vesicles (Figure 3 b i ) (6, 44, 5658, 78, 79). Some of these structures take up extracellular horseradish peroxidase or FM dyes, suggesting their endocytic origin (Figure 3 b i ).…”
Section: Endocytosis Modes: Supporting Evidencementioning
confidence: 99%
“…Some of these structures take up extracellular horseradish peroxidase or FM dyes, suggesting their endocytic origin (Figure 3 b i ). Imaging reveals large fluorescent spots that may correspond to endosome-like structures taking up extracellular dyes (Figure 3 b ii ) (7983). Endosome-like structures may be generated by bulk endocytosis or by vesicle-vesicle fusion.…”
Section: Endocytosis Modes: Supporting Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, when preparations were rested after 15 min stimulation, the cisternae disappeared and SVs reappeared, suggesting the SVs could have derived from the cisternae [1]. Since this initial seminal study, a considerable number of studies have demonstrated that ADBE also occurs in rat hippocampal [6,17] and cerebellar granule [18] neurons, lamprey reticulospinal synapses [5], mouse calyx of Held [19] and auditory inner hair cells [20], snake [21] and Caenorhabditis elegans motor terminals [22], and goldfish bipolar neurons [8].…”
Section: Adbe At Neuronal Synapsesmentioning
confidence: 99%
“…With a pKa of 6.1, Cypher 5 is only fluorescent under acidic conditions. Traditionally, Cypher5 has been conjugated to antibodies to study receptor internalization and the pH change in the endocytic compartments (Adie et al, 2002; Nordberg et al, 2007; Wenzel et al, 2012). However, antibody conjugation is not practical and readily available.…”
Section: Introductionmentioning
confidence: 99%